The Oliver Stone experience - Seitz, Matt Zoller 1968- (Abrams, an imprint of Abrams, 2016)
"Stone himself serves as guide to this no-holds-barred retrospective--an extremely candid and comprehensive monograph of the renowned and controversial writer, director, and cinematic historian in interview form"--Back cover